Development of an Attitude Scale of Mathematics and Science Teachers towards Mistake and Instant Feedback to the Mistake: A Validity and Reliability Study - Turkdogan, Ali (Asian Journal of Education and Training, 2020)
The purpose of the research is to develop a valid and reliable attitude scale that can measure the attitudes of math and science teachers (315) and teacher candidates (105) towards mistakes and instant feedback. In the validity studies, the exploratory factor analysis was made with the SPS1S 8.0 package program after that the confirmatory factor analysis was made with Lisrel 8.8 software. To develop the scale; 1. Creation of Item Pool 2. Obtaining Expert Opinion, 3. Creation of Pre-Trial Form 4. Factor Analysis is made. According to factor analysis; Kaiser Meyer Olkin (KMO) rate; .808; Bartlett test result: 2148,354; Cronbach alpha reliability coefficient for the whole scale: .829. According to confirmatory factor analysis: Root Mean Square Error of Approximation (RMSEA) .022 (<.05); p-Value for Test of Close Fit .00 (<.05), standardized root mean square residual (SRMR) .014, Goodness of Fit Index (GFI) .75, Adjusted Goodness of Fit Index (AGFI) .69; Normed Fit Index (NFI) .91; Relative Fit Index (RFI) .78; Incremental Fix Index (IFI): .83; Parsimony Goodness of Fit Index (PGFI): .62; Degrees of Freedom: 760; Root Mean Square Residual (RMR): 2.07 and NonNormed Fit Index (NNFI): .88. According to research findings, attitude scale is valid and reliable so it can be used to determine math and science teachers and teacher candidates positive and negative attitudes toward mistake and giving instant feedback to mistake.